2014
DOI: 10.15252/embj.201489499
|View full text |Cite
|
Sign up to set email alerts
|

ARGONAUTE 6 bridges transposable element m RNA ‐derived si RNA s to the establishment of DNA methylation

Abstract: Transposable elements (TEs) generate mutations and chromosomal instability when active. To repress TE activity, eukaryotic cells evolved mechanisms to both degrade TE mRNAs into small interfering RNAs (siRNAs) and modify TE chromatin to epigenetically inhibit transcription. Since the populations of small RNAs that participate in TE post-transcriptional regulation differ from those that establish RNA-directed DNA methylation (RdDM), the mechanism through which transcriptionally active TEs transition from post-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
115
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(126 citation statements)
references
References 49 publications
8
115
0
Order By: Relevance
“…It was also shown that AGO4 and AGO6 differ in their subnuclear colocalization and in interactions with Pol II and Pol IV, and it was proposed that they may act sequentially to mediate DNA methylation . AGO6 also binds RDR6-dependent 21-to 22-nucleotide siRNAs generated from transcriptionally active TEs and is thought to trigger the initiation of de novo TE DNA methylation (Nuthikattu et al, 2013;McCue et al, 2015), which may provide a link between PTGS and TGS of TEs.…”
Section: Ago2/3/7 Cladementioning
confidence: 99%
“…It was also shown that AGO4 and AGO6 differ in their subnuclear colocalization and in interactions with Pol II and Pol IV, and it was proposed that they may act sequentially to mediate DNA methylation . AGO6 also binds RDR6-dependent 21-to 22-nucleotide siRNAs generated from transcriptionally active TEs and is thought to trigger the initiation of de novo TE DNA methylation (Nuthikattu et al, 2013;McCue et al, 2015), which may provide a link between PTGS and TGS of TEs.…”
Section: Ago2/3/7 Cladementioning
confidence: 99%
“…Although it is well established that 24-nucleotide siRNAs can target RdDM, recently other types of siRNAs have also been implicated in directing RdDM. Diced 21-to 22-nucleotide TE siRNAs incorporate into AGO6 to target RdDM to active TEs (McCue et al, 2015), and when the Dicer proteins are absent, Dicer-independent longer RNAs can incorporate into AGO4 and then be subsequently trimmed to the 21-to 24-nucleotide size (Ye et al, 2016). Targeting of RdDM acts through an RNA scaffold at the target locus produced by the plant-specific Pol V, which transcribes methylated regions ( Figure 2A; Johnson et al, 2014).…”
Section: Tes Near Genesmentioning
confidence: 99%
“…Several articles have recently described two mutually exclusive classes of TEs in Arabidopsis: one where CHH methylation is maintained by CMT2 and the other where CHH methylation is constantly targeted via RdDM ( Figure 5) (Stroud et al, 2014;Li et al, 2015;McCue et al, 2015). These two distinct classes represent (1) TEs present in large constitutive heterochromatic blocks found in the pericentromere, knobs, and TE islands regulated via CMT2 and (2) TEs near genes regulated by RdDM and the DNA methyltransferase DRM2 (see above).…”
Section: Tes At the Pericentromere Knobs And Te Islandsmentioning
confidence: 99%
See 1 more Smart Citation
“…AGO6 mediates RNA-directed DNA methylation Havecker et al, 2010;Eun et al, 2011;McCue et al, 2015). AGO6 participates in RNA-directed DNA methylation of transcriptionally active transposable elements through incorporation of fragments of PTGS-targeted transcripts of transposable elements onto AGO6 (McCue et al, 2015).…”
Section: Ago6mentioning
confidence: 99%